2022
DOI: 10.3329/jbcps.v40i4.61877
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Infertile Males with Oligospermia: A Cross-sectional Comparative Study

Abstract: Introduction: The male factor responsible for infertility includes oligospermia. According to WHO criteria, oligospermia is sperm concentration less than 15 million per millilitre of semen. Vitamin D is a steroid hormone synthesized in the skin and derived from the diet. A serum level less than 20 ng/dl is regarded as vitamin D deficiency. The deficiency of vitamin D has been linked to many reproductive disorders. This study was designed to analyze the association between serum vitamin D level and oligospermia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Most research has focused on a total 25OHD. Regarding this indicator, our results are in agreement with the results of other authors who reported a significant decrease in total 25OHD levels in men with abnormal spermogram compared to men with normozoospermia (Holzer et al, 2022; Islam et al, 2022). A few studies did not find a significant difference in the total 25OHD levels between fertile and infertile men (Nasreen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on a total 25OHD. Regarding this indicator, our results are in agreement with the results of other authors who reported a significant decrease in total 25OHD levels in men with abnormal spermogram compared to men with normozoospermia (Holzer et al, 2022; Islam et al, 2022). A few studies did not find a significant difference in the total 25OHD levels between fertile and infertile men (Nasreen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%